2005
DOI: 10.1017/s0022112004002393
|View full text |Cite
|
Sign up to set email alerts
|

Droplet impact on a dry surface: triggering the splash with a small obstacle

Abstract: Droplet impact on a dry solid surface is investigated experimentally. A small obstacle made by layers of adhesive tape is located on the solid surface at some distance from the impact centre. The splashing of the drop starts at the tape, as a sheet of liquid shoots upwards. Angle, speed and dynamics of this liquid sheet are investigated as a function of the distance from the impact centre to the obstacle and its height. Reynolds and Weber numbers are kept constant. Volume-of-fluid simulations reproduce the exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
45
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(45 citation statements)
references
References 30 publications
0
45
0
Order By: Relevance
“…9 In other papers, the authors apparently refer interchangeably to the central part of the lamella and the curved end where surface tension acts. 8,[10][11][12] c͒ measurements of the rim thickness, which we report here, can be viewed as constraints on possible simplified models. Despite the theoretical predictions and relevance of the lamella thickness to understanding both spreading and splashing phenomena, there have been relatively few direct measurements, particularly at the time scale relevant for splashing.…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…9 In other papers, the authors apparently refer interchangeably to the central part of the lamella and the curved end where surface tension acts. 8,[10][11][12] c͒ measurements of the rim thickness, which we report here, can be viewed as constraints on possible simplified models. Despite the theoretical predictions and relevance of the lamella thickness to understanding both spreading and splashing phenomena, there have been relatively few direct measurements, particularly at the time scale relevant for splashing.…”
Section: Introductionmentioning
confidence: 84%
“…It is common in recent theories of splashing to assume that the lamella thickness is proportional to the thickness, ͱ t, of a viscous boundary layer, where is the kinematic viscosity of the liquid and t is the time after impact. [8][9][10][11][12] This same idea has also been used for film thickness after impact on a thin liquid film. 13 A functional form for the lamella thickness is also essential for theories of film spreading after droplet impact.…”
Section: Introductionmentioning
confidence: 99%
“…The influence of the substrate on the spreading and splashing has been studied in [126,[137][138][139][140][141]. Recent research by Nagel's and Brenner's groups has identified that the compressibility of the gas, here air surrounding the droplet [142,143] affects the splashing.…”
Section: An Example Of Current Capabilities Of Computational Fluid Dymentioning
confidence: 99%
“…However, some authors have looked at smooth solid substrates containing a single obstacle (Delbos et al 2010;Ding & Theofanous 2012;Lorenceau & Quéré 2003;Roisman et al 2010;Josserand et al 2005), e.g., the impact of a droplet near an open-ended hole (pore), revealing different flow behaviour depending on the impact location. For a centred impact, the inner part of the droplet will enter the pore and the remaining liquid will spread (Delbos et al 2010;Ding & Theofanous 2012).…”
Section: Introductionmentioning
confidence: 99%